3D flow-focusing microfluidic biofabrication: One-chip-fits-all hydrogel fiber architectures. (June 2021) - Guimarães, Carlos F.; Gasperini, Luca; Marques, Alexandra P.; Reis, Rui L.
Highlights: 3D flow-focusing microfluidics as a new, widely adaptable biofabrication tool. One single chip for creating multiple, tunable hydrogel fiber shapes. Recreation of complex 3D cancer microenvironments (cancer-on-a-fiber). Continuous fabrication of endothelial-laden fibers and networks. Multi-chemistry tissue engineering to carry and stimulate stem cells. Abstract: The microfluidic manipulation of hydrogels is a powerful tool to recapitulate functional biological architectures. A wide range of flow configurations and chip designs have been employed to create microfibers with increasingly complex shapes and compositions requiring individually engineered setups. Distinctly, we demonstrate how one single 3D hydrodynamic flow-focusing chip can be used to obtain a continuous flow of hydrogel precursors, which rearrange themselves based on viscosity and applied pressures. These can crosslink into fibers with a variety of new multi-compartment shapes down to yet-unreported minimal dimensions. To prove the potential of 3D flow-focusing for the biofabrication of complex, multi-compartment structures, we tuned material properties and flow conditions to obtain ribbon-like cancer/basement-membrane/stroma models; core-shell vascular-like structures and networks; and multi-chemistry fibers integrating stem cells, biomaterials, and pro-differentiation hydrophobic molecule depots. This innovative biofabrication method can be valuable for the recreation of a broad range of complex biological architectures and micro-modeling of distinct 3D environments. Graphical abstract: Image, graphical abstract